Supravalvular aortic stenosis - Novel pathogenic ELN variant in siblings with a wide spectrum of clinical cardiovascular features and a long follow-up from infancy to adulthood - Keskinen, Sini; Niemelä, Jussi; Koillinen, Hannele; Boldt, Talvikki; Arola, Anita (Elsevier BV, 2025)
Background: Supravalvular aortic stenosis (SVAS) is an autosomal dominantly inherited congenital cardiovascular disease caused by disruption of elastin gene (ELN), encoding elastin, an essential component of elastic arteries. It usually affects the middle layer of the wall of the aorta but also the pulmonary and coronary arteries may be affected.
Methods: We report a family with six affected siblings who were closely followed up from infancy to early adulthood at a pediatric cardiology outpatient clinic. Whole-exome sequencing was performed using DNA of the index patient. Targeted variant testing was performed for other family members.
Results: The affected siblings presented with a wide spectrum of clinical features of SVAS, ranging from mild pulmonary artery stenosis with or without pulmonary artery branch stenoses to severe supravalvular aortic obstruction and coronary artery stenosis with fatal outcome. Genetic analysis identified a novel pathogenic 1-bp deletion c.1983delG, p. (Pro662Leufs*13) in the ELN gene. Males tended to have a more severe cardiac disease than females. However, if interventions were successful during infancy or early childhood, the outcome was fairly favorable. Moreover, supravalvular pulmonary stenosis, even when combined with a stenotic pulmonary valve and severe pulmonary artery branch stenoses, tended to resolve during follow-up.
Conclusions: We describe a family with six siblings showing elastin arteriopathy with variable disease severity and outcome. A novel pathogenic ELN gene variant was detected in five of them, indicating that there are obviously yet unknown genetic and environmental modifying factors that affect the severity and outcome in individual patients.